Rethinking nineteenth-century literary culture: British worlds, southern latitudes and hemispheric methods. (June 2023) - Comyn, Sarah; Fermanis, Porscha
Drawing on hemispheric, oceanic, and southern theory approaches, this article argues for the value of considering the nineteenth-century literary cultures of the southern settler colonies of Australia, New Zealand, and South Africa from within an interconnected frame of analysis. First, because of their distinctive historical and structural conditions; second, because of the density of their interregional networks and relations across intersecting oceanic spaces; and third, because of the long history of racialized imperialist imaginaries of the south. This methodological position rethinks current approaches to "British world" studies in two important ways: first, by decoupling the southern settler colonies from studies of settler colonialism in North America; and second, by rebalancing its metropolitan and northern locus by considering south-south networks and relations across a complex of southern islands, oceans, and continents. Without suggesting either that imperial intercultural exchanges with Britain are unimportant or that there is a culturally homogenous body of pan-southern writing, we argue that nineteenth-century literary culture from colonial Australia, New Zealand, and South Africa — what we call a "southern archive" — can provide a counterbalance to northern biases and provide new purchase on nation-centred literary paradigms — one that reveals not just south-south transnational exchanges and structural homologies between southern genres, themes, and forms, but also allows us to acknowledge the important challenges to foundational accounts of national literary canons initiated by southern theory and Indigenous studies scholars.